(untitled) (GYMNASIUM, 2019)
This theme was chosen to verify the role of programs using gymnastics means, in particular applicative exercises procedures, highlighting their effectiveness, both from a therapeutic, and a prophylactic point of view. The purpose of the research was to identify and improve the scoliosis through a physical therapy treatment, by applying applicative exercise programs. The applicative intervention was conducted over a five months period, between January and May 2016, during physical education classes. At the end of the research, it can be said that the initial hypotheses were confirmed. After applying the intervention programs designed on the basis of applicative exercises, the recorded results and the statistical interpretation of the final values, compared to the initial ones, show an improvement of the identified scoliotic postures.